The sociodemographic patterning of opposition to raising taxes on tobacco and restricting tobacco advertisements in Argentina. Issue 4 (April 2015) - Konfino, J.; De Maio, F.; Ondarsuhu, D.; Goldberg, L.; Linetzky, B.; Ferrante, D.
Abstract Background Argentina has enacted important tobacco control initiatives in recent years. Yet little is known about the social patterning of attitudes toward tobacco control. Research is needed to explore what predicts opposition to tobacco control initiatives such as higher taxes on tobacco and the prohibition of tobacco advertising. Study design Secondary analysis of Argentina's Global Adult Tobacco Survey (N = 6645). Methods Binary logistic regression analysis examining opposition to raising tobacco taxes and banning tobacco publicity. Models were stratified by smoking status. Results Respondents generally indicated very little opposition to either tobacco control measure, with only 15.6% of respondents opposed to increasing taxes on tobacco products and 9.6% opposed to banning tobacco advertisements. Smoking status is the most important predictor of opposition to increasing taxes (OR = 7.85, 95% CI = 6.60–9.34) and banning advertisements (OR = 1.72, 95% CI = 1.39–2.11). Opposition to these measures is most likely among young respondents (aged 15–24) and least likely among older age groups (55–64 and 65 or over), compared to the 25–34 age group. Stratified models suggest that the effect of age may be different for smokers and non-smokers. Low income is a significant predictor of opposition, but only in stratified models for smokers. Conclusion There is general support for stronger tobacco control measures in Argentina. Opposition to raising taxes on tobacco products and banning tobacco advertisement appears to be concentrated among young smokers with low and medium levels of household income.